Determination of Some Pharmaceutical Compounds Using Silanized Algerian Bentonite (B1100) as Support in Gas Chromatographic Analysis - LAHMEK, M.; RAMADAN, A.A. (Asian Journal of Chemistry, 2010)
Some pharmaceutical compounds such as butoform, caffeine, menthol, methyl paraben, phenol, propyl paraben and nabumeton were determined using support on the basis of Algerian bentonite in gas chromatographic analysis. The support was prepared by thermal treatment at 1100 ºC and chemically by 6 N HCl (B1100). The B1100 granules, with diameter range 125-150 μm and specific surface area 12 m2/g, were silanized with dimethylchlorosilane. The results were characterized by high accuracy and sensitivity with relative standard deviation not exceeding 4.7 %.